THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION ON PERFORMANCE WITH TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH IN PUBLIC SERVICE AGENCIES OF JAMBI PROVINCE - Kusumathias, Intan Putri; Rahayu, Sri; Wiralestari, Wiralestari (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The financial accounting system of the Public Service Agency (BLU) is created to provide detailed information about BLU's financial situation, its capacity to obtain economic resources, expenses incurred, sources and use of funds, and compliance with regulatory standards. This research examines the impact of implementing an accounting information system on performance using the Technology Acceptance Model (TAM) approach at a Public Service Agency in Jambi Province. Employing a survey method through online questionnaires, the study focuses on variables such as perceived usefulness, perceived ease of use, and performance. The participants include 237 users of the Accounting Information System at BLU in Jambi Province, with 233 questionnaires returned and processed. The analytical tool used is SMART PLS. The results indicate that perceived ease of use, perceived usefulness, and acceptance of the Accounting Information System significantly affect its adoption, while perceived ease of use does not significantly impact performance. Perception of usefulness significantly influences performance. Individual performance achievement is linked to task completion with the support of information systems. While perception of ease of use can directly affect performance, it can also have an indirect impact through acceptance of the Accounting Information System as a mediator.